Examination of the Factors Influencing Speech Delays in Children Ages 2 to 5 Years - Amalia, Rizki; Afrika, Eka; Irdan, Irdan; Handayani, Sri (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Speech Delay is a condition experienced by children which can cause them to experience speech and language delays. Even though the child understands what someone is saying, the child has difficulty saying it again. Children who experience speech delay can be caused because one of the organs (brain, ear and mouth) is disturbed, causing their speech process to be disrupted. Research conducted in the United States of America, the number of children who experience speech delay is 5% to 8% aged 4.5 years. The purpose of this study was to determine the relationship between parenting style, child gender and intensity of simultaneous use of getged with speech and language delays. This study used an analytic survey method with a cross sectional approach. This research was carried out at the Muara Enim Health Center in 2022. With a sample size of 30 respondents, the sampling technique used the accidental sampling technique. The variables studied were independent (the intensity of gadget use, the sex of the child and parenting style) and dependent (speech delay and language delay). The results of the chi-square statistical test on the intensity variable of gadget use obtained ρ value = 0.012, the results of the gender variable test obtained ρ value = 0.022 and parenting pattern variable obtained ρ value = 0.031 less than α = 0.05 indicating that there is a significant relationship between intensity use of gedegt with speech delay and speech delay at the Muara Enim Health Center in 2022